Kebutuhan Pelayanan Air Bersih Kabupaten Maros Tahun 2017-2037 - Egidya Caesarisma; Muhammad Fathien Azmy; Yashinta Kumala Dewi Sutopo (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2018)
Clean water is one of the basic infrastructures supporting human daily activities in general, community clean water services in an area are strongly influenced by availability factors, clean water sources and the number of people to be served. In Maros Regency water supply has not been able to meet the needs of clean water community, which is indicated by the percentage of the population served by clean water by the PDAM in 2017 only 34% of the total 117,650 people. The purpose of this research is to find out how much the clean water needs of the Maros Regency community for the next 20 years, whether it has been fulfilled with the current system and to find out what factors influence the clean water service in Maros Regency. The analytical method used is quantitative analysis to calculate population projections using multiple interest formulas and analysis of the population's need for clean water and analysis using the expert judgment method to determine the weight factor of the Maros Regency clean water service based on the opinions of experts who are then processed using expert choice tools. The recommendations produced in this study are to add clean water sources and make improvements and management of water treatment from source to distribution to the community.